PERANCANGAN DAN EVALUASI SISTEM PEMBELAJARAN INTERAKTIF MENGGUNAKAN METODE SYSTEM USABILITY SCALE (SUS) DAN USER EXPERIENCE QUESTIONNAIRE (UEQ) - Permatasari, Ainun; Septiadi, Jaka (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2026)
Advances in digital technology call for learning systems that not only deliver content but also enhance student engagement and self-directed learning. However, most existing digital learning systems do not fully support the process of Self-Regulated Learning (SRL). This study aims to design and evaluate a prototype of an SRL-based interactive learning system using a User-Centered Design (UCD) approach. The prototype was developed using Figma and tested on 100 vocational high school students aged 16–18 via the Maze platform. The evaluation was conducted using the System Usability Scale (SUS) and the User Experience Questionnaire (UEQ). The results showed a 100% task success rate, with an SUS score of 75 falling into the “acceptable” category and UEQ results indicating a positive user experience across all dimensions. These findings indicate that the designed system has good usability and is capable of providing a learning experience that supports student engagement and independence in technology-based learning.   Keywords: Interactive Learning System; Self-Regulated Learning; System Usability Scale; User Experience Questionnaire; User Centered Design.